“What good are all these divisions in Islam?”. Everyday Islam and normative discourses in Daghestan - Kaliszewska, Iwona (Contemporary Islam, 2020)
Republic of Daghestan is the most multiethnic and troublesome region in the Russian Federation. The social, religious and political landscape of this republic has radically changed over the last two decades. Daghestan appears in academic and analytical papers mostly in relation to terrorism or security issues. The everyday religiosity is, for the most part, out of the picture. This paper aims to fill the gap by focusing on everyday Islam in this republic. It is intended as a contribution to the anthropology of Islam and post-Soviet area studies. What can we learn about the social changes in the given setting if we re-focus our attention from religious figures, organizations and institutions and drift towards the everyday perceptions and experiences of ordinary Muslims, towards religiosity as embedded in everyday life but not within a clearly identifiable group? Religious life in Daghestan is usually viewed through official categories of “traditional Islam” and “non-traditional Islam”, the former equated with “Sufism”, the latter with “Wahhabism”. As will be clear from this paper these theology driven qualifiers are usually used in a secular sense, with no clear religious content attached to them. However, as a part of powerful discourses they affect religious life of ordinary Muslims. How do they relate to these categories? In my paper I show how attitudes towards Salafi-oriented Muslims changed in Daghestan between 2007 and 2017: they drifted from being informed by official categories to being informed by everyday experiences. I will also show how and in what contexts Daghestani Muslims engaged and played with the categories, bringing in some comparisons with late-Socialism. Eventually, I will engage with the concept of “everyday Islam”, its potentials and limitations as an analytical category used for the analysis of social life in the North Caucasus where an organized religious and political activity is limited and where the clearly identifiable groups are not those that are behind the most vital social changes. The paper is based on ethnographic fieldwork conducted between 2007 and 2017 among Daghestani Muslims in Makhachkala and beyond.